ANALISIS PROSES PEMBELAJARAN MELALUI LESSON STUDY FOR LEARNING COMMUNITY BERBASIS TRANSKRIP BASED LEARNING ANALYSIS (TBLA) - Veny Agustini Prianggita; Hendayana, Sumar; Jihaduddin; Riswanto, Dody (Fakultas Agama Islam, Universitas Mathla'ul Anwar, 2022)
Lesson Study for Learning Community (LSLC) activities have the potential to encourage many parties to do their best in improving the quality of learning. LSLC activities based on Transcript Based Learning Analysis (TBLA) are a way to enable teachers to sharpen their learning lenses intensively and comprehensively from various perspectives. The problems studied were